Nanoscale Synergetic Effects on Ag–TiO2 Hybrid Substrate for Photoinduced Enhanced Raman Spectroscopy (PIERS) with Ultra‐Sensitivity and Reusability. Issue 50 (22nd September 2022) - Shondo, Josiah; Veziroglu, Salih; Tjardts, Tim; Sarwar, Tamim Bin; Mishra, Yogendra Kumar; Faupel, Franz; Aktas, Oral Cenk
Abstract: Here, a 4N‐in‐1 hybrid substrate concept (nanocolumnar structures, nanocrack network, nanoscale mixed oxide phases, and nanometallic structures) for ultra‐sensitive and reliable photo‐induced‐enhanced Raman spectroscopy (PIERS), is proposed. The use of the 4N‐in‐1 hybrid substrate leads to an ≈50‐fold enhancement over the normal surface‐enhanced Raman spectroscopy, which is recorded as the highest PIERS enhancement to date. In addition to an improved Raman signal, the 4N‐in‐1 hybrid substrate provides a high detection sensitivity which may be attributed to the activation possibility at extremely low UV irradiation dosage and prolonged relaxation time (long measurement time). Moreover, the 4N‐in‐1 hybrid substrate exhibits a superior photocatalytic degradation performance of analytes, allowing its reuse at least 18 times without any loss of PIERS activity. The use of the 4N‐in‐1 concept can be adapted to biomedicine, forensic, and security fields easily. Abstract : A 4N‐in‐1 hybrid substrate (nanocolumnar structures, nanocrack network, nanoscale mixed oxide phases, and nanometallic structures) is developed for ultrasensitive and reliable photo‐induced‐enhanced Raman spectroscopy. The prepared 4N‐in‐1 hybrid substrate concept is an ideal platform for the detection of ultra‐trace levels of various small molecule analytes with long‐term stability and photocatalytic self‐cleaning performance.